Partikel Karbon Aktif Tempurung Kelapa Sawit dan Zeolit Alam Bayah Teraktivasi Terhadap Penurunan Turbidity dan Bakteri Coliform pada Sungai Cibanten - Suhirman, Suhirman; Surahman, Iman; Toni, Afri Andrean; Iqbal, Muhammad (UNIVERSITAS ISLAM SYEKH YUSUF TANGERANG, 2025)
Zeolit alam Bayah Activated (ZeOavd) and Carnel shell activated carbon using pretretment with hidrogen peroxide (KATKS/H2O2) are porous materials for application multimedia filters in river water treatment. The purpose of this study to reduce turbidity and total coliform in the Cibanten River using ZeOavd and KATKS/H2O2. Sampel of Cibanten River flowing at 100 ml per minute into the KATKS/H2O2 filter tank and then flows into the ZeOavd material. Sampling was carried out 5 minutes after overflow for turbidity and total coliform analysis. The best results were checked until 5 to 120 minutes in range of 15 minute . The best results showed of Cibanten River water contacted with 2 kg of KATKS/H2O2 and 2 kg of ZeOavd was able to reduce total coliform from 240 MPN/100 mL to 0 240 MPN/100 mL. In addition, it was able to reduce turbidity from 57.1 NTU to 1.60 NTU. Keywords : Cibanten River; Zeolite; KATKS; Tubidity and Total Coliform .